The impact of emotional intelligence on ethical judgment. Issue 6 (14th June 2018) - Hopkins, Margaret; Deepa, R.
Abstract : Purpose: The purpose of this paper is to investigate the important relationships between emotional intelligence (EI) and ethical decision making (EDM). Design/methodology/approach: Participants were 100 students from MBA programs in the USA and India who completed two surveys: one measuring their EI, and the second their use of four different ethical perspectives in three scenarios. Multiple regression analyses were performed to discover relationships between overall EI, certain dimensions of EI and their ethical judgments. Findings: The authors' results found that the composite EI score as well as the EI subscale of decision making were both significantly related to the relativism ethical perspective. Age was an additional significant factor for EI and EDM. Research limitations/implications: Future research should attempt to replicate these findings among different managerial levels, industries and countries to further understand the distinctive relationships between EI and ethical judgments. Practical implications: This study highlights the importance of integrating EI and ethical judgment within corporate training programs and business school curricula, as important is the emphasis on moving the subject of ethical judgment from one of awareness to sustained ethical behavior through accountability. Originality/value: This study contributes to the literature by identifying how EI and its decision-making subscale are significant to EDM.